Digital Literacy and Digital Technology in Post Covid-19 Era: Indonesian Educators’ Experiences and Opinions - Paramahita, Ketut Bayu Catur; Utami, I G A Lokita Purnamika; Santosa, Made Hery (Jurnal Ilmiah Pendidikan Profesi Guru, 2023)
Advance in technology has rarely been accompanied by adequate thinking skills and adaptation, especially in Indonesia, where there is a trend of low-level digital literacy among the populace. Therefore, this research aims to analyze Indonesian educators’ opinions on the development of digital literacy and the experience of using digital technology to facilitate teaching and learning activities before, during, and following the end of the online learning policy during the Covid-19 pandemic. This research is qualitative research using phenomenological research design. Data were gathered by using semi-structured interviews with 11 respondents, consisting of 6 college lecturers and 5 high-school teachers. The data were analyzed by using thematic analysis. The result of the data analysis shows that the respondents have generally positive views on digital literacy development, were familiar with digital technology even before the pandemic, and were able to produce digital content for teaching and learning. Zoom and Google Meeting were also discovered to be the most used applications to facilitate learning. The majority of the respondents have also shown interest in the further use of digital technology, asynchronous learning, and distance learning after the end of The Covid-19 Pandemic. Problems mentioned in developing digital literacy include the lack of infrastructure and digital divide among students, alongside the misuse of digital technology for entertainment over learning. Therefore, this research concluded that Indonesian educators have positive opinions about the development of digital literacy, and positive experiences with digital technology.